Internet generation in religious cyberspace: worldview challenges of the digital age - Ірина Ломачинська; Юлія Гришина (Cхід, 2024)
The article is devoted to the analysis of the peculiarities in the perception of reli-gious cyberspace by the Ukrainian Internet generation. The relevance and novelty of the research consists in determining the specifics of the religious cyberspace func-tioning in the context of the spiritual and intellectual needs of the Internet generation, clarifying the essence of worldview challenges that the globalized digital age poses to young people in the religious cyberspace. The peculiarities of the religious cyber-space formation in the Ukrainian and world context are analyzed. It is noted that functioning of the virtual religious space can be considered through several key as-pects: online worship, virtual prayers, educational programs of spiritual develop-ment, platforms for discussing religious topics and sharing experiences in social networks, electronic libraries, digital missionary programs, virtual pilgrimage, the use of various mobile applications for prayer practices, etc. The peculiarities of the digi-tal religion phenomenon are defined as a dynamic process in which religious groups and individuals adopt digital technologies and adapt to them depending on their values and capabilities. The essential features of the Internet generation, the specif-ics of its intellectual and spiritual requests, and self-presentation in religious cyber-space are analyzed. The challenges and dangers produced by religious cyberspace in the modern globalized era are characterized. The Conclusions state that religious cyberspace provides the Internet generation with unique opportunities for spiritual growth, learning, communication and active participation in religious life, however, the safe use of religious cyberspace is possible through digital culture and continu-ous self-education. Among the measures of counter social manipulations and reli-gious extremism in the online space are educational programs aimed at raising awareness of different religions and culture, which promotes tolerance and mutual understanding, development of media culture and critical thinking among users of religious cyberspace, active use of social media to spread positive and truthful reli-gious content, creation of mechanisms for checking facts and exposing disinfor-mation in the religious sphere.